O princípio da eficiência como instrumento de racionalização do poder punitivo penal na criminalidade econômica - Renata Rodrigues de Padua (2018)
In this research, the principle of efficiency is analyzed in the scope of economic crime and in the framework of the post-industrial society. We refer to the Economic Analysis of Law - AED, an area in which crime presents itself as one of the classes of inefficient acts. The thesis aims to demonstrate that the principle of efficiency is capable of contributing to the rationalization of punitive power, adding to other concepts already widely used for the same purpose; as is the case of the harm principle, when understood in a way that allows it to perform a citizen's guarantee function. Therefore, the principle of efficiency must be integrated with the other elements that primary criminalization, that is, the activity of the criminal legislator. On the one hand, under the negative axis, the principle of efficiency may: (a) prevent the creation of criminal offenses; and (b) exclude existing criminal offenses. On the other hand, under the positive axis, it may: (a) allow the creation of criminal offenses; and (b) (re) interpret criminal offenses. In both cases, the efficiency principle presents itself as a theoretical resource capable of criticizing criminal law.